2023
DOI: 10.1101/2023.03.01.530707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring neural tracking of acoustic and linguistic speech representations in individuals with post-stroke aphasia

Abstract: Aphasia is a communication disorder that affects processing of language at different levels (e.g., acoustic, phonological, semantic). Neural tracking of continuous speech, such as a story, allows to analyze brain responses to acoustic and linguistic properties. Even though neural tracking of speech measured via EEG may be an interesting tool to study aphasia in an ecologically valid way, this method has not yet been investigated in individuals with stroke-induced aphasia. Here, we explored processing of acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 123 publications
1
7
0
Order By: Relevance
“…We describe the behavioral tests of interest below. In previous studies at our research lab, IWA performed worse on these tests compared to healthy controls (Kries et al, 2023a,b; Mehraram et al, 2024).…”
Section: Methodsmentioning
confidence: 56%
See 3 more Smart Citations
“…We describe the behavioral tests of interest below. In previous studies at our research lab, IWA performed worse on these tests compared to healthy controls (Kries et al, 2023a,b; Mehraram et al, 2024).…”
Section: Methodsmentioning
confidence: 56%
“…The presented sample is a subset of prior studies (Kries et al, 2023a;Mehraram et al, 2024), comprising 39 native Flemish IWA (13 female participants, mean age = 69.6 y/o, sd = 12.4 y/o) in the chronic phase (≥ 6 months) post-stroke. Compared to these prior studies, one participant was excluded as we lacked accessible brain scan data.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence from primary progressive aphasia (PPA; Dial et al, 2021 ) demonstrated an increased CTenv in theta but not delta compared to neurotypicals, implying that people with PPA may rely more on acoustic properties during continuous speech processing. To date, this is one of the few studies that investigate CTenv in adult neurogenic language disorders (see De Clercq et al, 2023 ; Kries et al, 2023 ). Thus, the association between CTenv and language impairments as measured by aphasia severity is, to our knowledge, yet to be examined.…”
Section: Introductionmentioning
confidence: 99%